Application of condition coherence factor based on truncated composite method in ultrasound imaging. (May 2022) - Li, Xitao; Wang, Ping; Li, Qianwen; Du, Tingting; Luo, Ciyong
Highlights: We propose a condition coherence factor (CCF) based on the sign consistency of echoes. A truncated composite CCF (TC-CCF) is further proposed to improve the imaging quality. In TC-CCF, the truncation threshold is calculated to suppress the dark-region artifacts caused by CF. The results show that TC-CCF is superior to the traditional CF in resolution and speckle quality. Abstract: The coherence factor (CF) can improve the image contrast and side lobe suppression ability of traditional delay and sum (DAS) beamformer. However, it always leads to dark-region artifacts. In this paper, in order to reduce the dark-region artifacts while maintaining the image resolution and contrast as much as possible, a truncated-composite-based condition coherence factor (TC-CCF) is proposed for ultrasound imaging. Initially, the condition coherence factor (CCF) is defined as the ratio between the number of sampling time which should satisfy the condition of sign consistency and the total number of sampling time within the duration of a transmitting pulse. Then, setting a truncation threshold to truncate the CF and CCF, and the proposed truncated-composite condition coherence factor is obtained by combining the two truncated coherence factor. To evaluate the performance of the proposed methods, the simulation, the geabr_0 experiment, and the in vivo rat mammary tumor study is conducted. The simulated cyst indicates that TC-CCF can obtain better performance than CF and SCF in speckle quality. The geabr_0 experimental results demonstrate that the TC-CCF can gain 34.1% lower full width at half-maximum (FWHM) and 41.7% higher contrast ratio (CR) than traditional DAS. Furthermore, for experimental cysts, a maximal improvements of noise contrast ratio (CNR) and speckle signals-to-noise ratio (sSNR) is 137% and 114.5% respectively. In general, the proposed methods can effectively address the inherent limitation of the standard CF to improve the speckle quality.